التوسعة الفردية في ضوء آيات القرآن الكريم (دراسة في آراء المفسرين و العلماء) (Journal of the College of Basic Education, 2025)
The Holy Quran presents to man a complete and comprehensive system for the individual’s life, whether it is related to beliefs and morals, or to individual and cognitive behavior. This is done with the aim of recognizing the reality of human existence, which in turn leads to the difference in his path and behavior in life according to this understanding. Through it, his individual, social, psychological, and political path is determined in a manner that is consistent with that understanding. The topic gains its importance from this cognitive and path-oriented aspect, so the researcher chose the title: (Individual expansion through the verses of the Holy Quran (A study of the opinions of interpreters and scholars) for the importance of the topic in human life in general, and the study adopted the descriptive-analytical approach to achieve this goal. The researcher concluded that individual expansion in the Holy Quran includes various fields, including individual moral expansion, economic expansion, administrative, political, and social expansion to achieve divine succession on earth, and there are many terms that indicate individual expansion in the Holy Quran, including: knowledge, striving and work, purification, cooperation, and building the earth, management, etc.